Secreted Aspartyl Proteinase[SAP] Enzyme Proï¬le on Vulvovaginalis Candidiasis Patients isolates - Nugrahaeni, Diah; Agusni, Indropo; Ervianti, Evy (Faculty Of Medicine Airlangga University, 2015)
Background: Vulvovaginalis candidiasis (VVC) is an infection caused by various types of Candida, themost is Candida albicans. Candida produces two main enzymes that play a role in virulence, the secreted aspartyl proteinase (SAP) enzyme and the phospholipase enzyme. SAP is most widely produced by Candida albicans,which is one of the main pathogenicfactor of Candida infection. SAP is often found in cases of recurrent candidiasis vulvovaginalis (RVVC) Purpose: To evaluatethe SAP activity produced by VVC patients isolates. Methods: Descriptive observational cross-sectional study was conducted on 21 VVC patients to determine the SAP enzyme levels in VVC patients in Sexually Transmitted Infection (STI) Division, Outpatient Clinic Of Dermatology and Venerology, Dr. Soetomo General Hospital, Surabaya.Vaginal smear was examined to determine levels of SAP and culture examination to determine the kind of candida spesies that causes VVC. Results: Total subject of study are 21 patients. Twelve ofÂ 21 patients had SAP > 20 mm in diameter, 7 patients with SAP < 20 mm in diameter, and 2 patients with negative results of SAP. Fifty patients due to Candida albicans, 6 patients caused by non-albicans. Nine patients were accompanied by diabetes mellitus (DM), 1 patients by genital affection, 2 patients by condylomata acuminata. Additionally obtained in 10 patients who had previously received treatment with the results diameter SAP > 20 mm and 7 patients with of SAP diameter < 20 mm, 2 patients showed negative results of SAP. Conclusions: SAP was mainly produced by Candida albicans. SAP became more active in VVC patients that accompanied by diabetes melitus, affectiogenitalis, condylomata acuminate, and also in some patients who have received prior antifungal therapy.Key words: secreted aspartyl proteinase, vulvovaginalis candidiasis, Candida albicans,